Perancangan User Experience Aplikasi Pendukung Evaluasi dan Analisis Proses Pembelajaran untuk Guru Berbasis Android dengan Metode User-Centered Design dan Design Solution - Lutfi Putra Gusrinda; Lutfi Fanani; Ahmad Afif Supianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Observation is a data collection technique, with the aim of recording important points of the observation process so that it can be evaluated and improve results. In the world of education, the application of observation is carried out to the teacher in the hope that the results of observations can find out what is happening and are lacking in the learning process. To help the observation process, we need a media to help the teacher by focusing the teacher's needs and needs in designing the media, so that the media can be used to help the observation process. This research aims at observation and recording media by using user experience as a race in the making of solution solutions. The method used to explore user experience is Human Centered Design which is a method of placing prospective users as the main center of research development. The steps taken consist of identifying the user's needs by creating a persona and empathy map, then identifying the tasks and goals of the user with a user journey. Then the process of implementing the solution design is done by creating a wireframe, screenflow and prototype design which will be tested using the usability testing method and the usability scale system testing. From the test it was produced that the effectiveness level was 100% and the efficiency of 0.1 goals / sec and the level of user satisfaction was 57.5 which was at a sufficient level. Thus, it can be concluded that the solution design has succeeded in providing a solution to the problem despite the lack of user satisfaction